2017
DOI: 10.1021/acsami.7b09464
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Processing of Na0.44MnO2 Cathode Material for the Development of Greener Na-Ion Batteries

Abstract: The implementation of aqueous electrode processing of cathode materials is a key for the development of greener Na-ion batteries. Herein, the development and optimization of the aqueous electrode processing for the ecofriendly NaMnO (NMO) cathode material, employing carboxymethyl cellulose (CMC) as binder, are reported for the first time. The characterization of such an electrode reveals that the performances are strongly affected by the employed electrolyte solution, especially, the sodium salt and the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 59 publications
5
43
0
Order By: Relevance
“…(Figure 3a,b) is mainly composed of sub-micrometric slabs of 100-400 nm width and 0.6-1.4 µm length. Hence, the particle morphology of SC-NMO is similar to that of Na 0.44 MnO 2 reported in our previous work [29]. However, the dimensions of the SC-NMO slabs are smaller and surfaces of the slabs are less defined as compared to SS-NMO (Figure 3c).…”
Section: Structural and Morphological Characterization Of The As Prepsupporting
confidence: 81%
See 2 more Smart Citations
“…(Figure 3a,b) is mainly composed of sub-micrometric slabs of 100-400 nm width and 0.6-1.4 µm length. Hence, the particle morphology of SC-NMO is similar to that of Na 0.44 MnO 2 reported in our previous work [29]. However, the dimensions of the SC-NMO slabs are smaller and surfaces of the slabs are less defined as compared to SS-NMO (Figure 3c).…”
Section: Structural and Morphological Characterization Of The As Prepsupporting
confidence: 81%
“…Figure 5 reports the cycling performance of the SC-NMO at increasing C rates (C/10, C/5, C/2, 1 C, 2 C and 5 C) and during the long-term cycling test at 1 C. In addition, selected potential profiles of SC-NMO, recorded at different C-rates and during the 1st and 2nd cycle at C/10 are also given. The galvanostatic cycling data are compared with SS-NMO to reveal the impact of the modified synthesis conditions [29]. The capacities at C/10 are approximately 115 mA h g −1 , i.e., in very good agreement with literature data and close to the theoretical capacity of 121 mA h g −1 .…”
Section: Structural and Morphological Characterization Of The As Prepsupporting
confidence: 70%
See 1 more Smart Citation
“…[40] It was recently reported that aN a 3 V 2 (PO 4 ) 2 F 3 cathode with NaCMC binder has excellent high-rate performance and cycle life (i.e., 75 mAh g À1 @70 Ca nd 79 %c apacity retention after 3500 cycles). [25,41,42] However,o pposite results have also been reported;f or example, as odium Prussian blue/PVDF electrode showed superiorc harge-discharge performance to that prepared with NaCMCb inder. [25,41,42] However,o pposite results have also been reported;f or example, as odium Prussian blue/PVDF electrode showed superiorc harge-discharge performance to that prepared with NaCMCb inder.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26] Cost-effectiveness and large-scale applications are emphasized for NIBs. [22][23][24][25][26] Cost-effectiveness and large-scale applications are emphasized for NIBs.…”
Section: Introductionmentioning
confidence: 99%